EFFECTS OF SUB-LETHAL EXPOSURE OF ALUMINIUM ON GROWTH AND METAL ACCUMULATION PATTERNS IN INDIAN MAJOR CARPS - H. Azmat; M. Javed; S. Abdullah (Journal of Animal and Plant Sciences, 2019)
During the present research trial, the growth responses of 240 day-old three fish species viz. Labeo rohita, Gibelion catla and Cirrhina mrigala under chronic (1/3 of LC50)exposures of Aluminium (Al)were determined. After 12 weeks metal exposure, gills, liver, kidney, intestine, skin, scales, bones and muscle were isolated for the determination of Al concentrations. G. catla gained significantly higher weight of 19.60±0.15 g, followed by that of C. mrigala(18.81±0.17 g) and L. rohita (18.10±0.15 g). All the experimental fish species, grown under contamination free (control) environment showed significantly better growth rate due to significantly maximum feed intakes than those grown under sub-lethal concentrations of Al. The sublethal exposure of Al to the three fish species caused significantly variable accumulation of metal in the body organs of test fish species. Fish liver, kidney and gills accumulated significantly higher Al as compared to other organs of fish.
Keywords: heavy metals; toxicity; Gibelion catla; growth; Labeo rohita; Cirrhina mrigala